On a beautiful vision of reading the book of the universe - Bańka, Józef (Folia Philosophica, 2004)
The author of the article proves that a double and maximalistic assumption is present in the concept of Nicholas of Kuza. This assumption says on one hand that what is single aims at becoming everything, and what is general - i.e. the Universe - aims at reflecting itself in every single thing on the other. All speculations, however, which are transferred from single things to the Universe and then to God, are merely a non-entitled extrapolation. That is why it is not a matter of coincidence that the principle of Anaxagoras that «God is everything, and everything is included in Him», adopted by Nicholas of Kuza and being a postulate of pantheism - leaves an unsettled difficulty in a shape of a fundamental antimony: pantheism - transcendence. A Pythagoresian unity associated with a number is the ultimate solution to this situation, thus a unity, which - being definitely the smallest coincides with [coincidere] the Greatest.